2021
DOI: 10.1186/s40691-021-00270-9
|View full text |Cite
|
Sign up to set email alerts
|

Can consumers’ gamified, personalized, and engaging experiences with VR fashion apps increase in-app purchase intention by fulfilling needs?

Abstract: While the development of virtual reality (VR) apps is trending among fashion retailers to cope with the COVID-19 pandemic and promote consumers’ online shopping, less is understood about whether and the way these new VR apps increase consumers’ in-app purchase. This study was designed to address this issue by applying self-determination theory within the context of Taobao Life, a 3D avatar-based and game-featured virtual world on the Taobao app. Specifically, we investigated (1) whether the extent to which a V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 84 publications
(95 reference statements)
0
16
0
Order By: Relevance
“…Further, it will extend current research which has predominantly examined self-reported data to study IAPs (e.g. Dinsmore et al, 2017;Lau and Ki, 2021). Therefore, the following research question guides the study:…”
Section: Studymentioning
confidence: 94%
See 2 more Smart Citations
“…Further, it will extend current research which has predominantly examined self-reported data to study IAPs (e.g. Dinsmore et al, 2017;Lau and Ki, 2021). Therefore, the following research question guides the study:…”
Section: Studymentioning
confidence: 94%
“…Dinsmore et al. , 2017; Lau and Ki, 2021) by examining the behavioral predictors of paying behavior under varying levels of daily usage behavior and social competition motivation.…”
Section: Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research emphasized the integration of gamification-based activities in various areas, such as gamification-based activities in the medical-care sector (Tuah et al, 2021), organization and well-being of employees (Hammedi et al, 2021), education domain (Mathew and Pillai, 2022;Sethi et al, 2021), retailing (Lau and Ki, 2021), tourism (Jang and Hsieh, 2021) and, banking (Nasirzadeh and Fathian, 2020). Existing studies provided evidence of a positive association of AR/VRbased gamification with brand loyalty (Hsu and Chen, 2018), brand attitude , brand awareness (Abou-Shouk, and Soliman,2021), brand engagement (Xi andHamari, 2020), brand involvement (Nobre andFerreira, 2017), brand love (Hsu and Chen, 2018a) and buying impulse (Zhang et al, 2020;Chawaa, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…System-related factors include the characteristics of VR environments identified by comparing the differences between VR and physical (Lombart et al, 2020 ; van Herpen et al, 2016 ; Waterlander et al, 2015 ) or online environments (Hsu et al, 2020 ) and examining the degrees of immersion driven by various types of hardware, such as head-mounted displays, body-tracking sensors, and motion-tracked controllers that enable walk-around navigation (Alshaer et al, 2017 ; Gorini et al, 2011 ; Lee & Chung, 2008 ; Shin & Shin, 2011 ). Similar to immersions, researchers have also explored other determinants that induce virtual experience for consumers, such as vividness and interactivity (Hur et al, 2019 ; Kang et al, 2020 ; Kim et al, 2021 ; Park et al, 2018 ; Violante et al, 2019 ), impressiveness (Peukert et al, 2019 ; Violante et al, 2019 ), and customization/personalization (Elboudali et al, 2020 ; Lau & Ki, 2021 ; Shuai et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%